MNGI-14. PROGNOSTIC FEATURES OF MALIGNANT MENINGIOMA: EVALUATION OF AGGRESSIVE MENINGIOMAS WITHIN A LARGE RURAL HOSPITAL SYSTEM DATABASE AND FIRST REPORT OF A METASTATIC CHORDOID MENINGIOMA TO THE LUNG. (11th November 2019) - Tosha Gatson, Na; Manikowski, Jesse; Bross, Shane; Hinger, Bradley; Mauer, Tian; Garcia, Tiffany; Lacroix, Michel; Mahadevan, Anand; Mongelluzzo, Gino; Vadakara, Joseph; Jaffar Kazmi, Syed A
Abstract: Meningiomas comprise 37% of primary brain tumors, arise extra-axially from the arachnoid cap cells, and are typically identified by classic imaging and histopathologic features. Blacks, females, and people age 65+ have higher incidence rate - partially correlated with hormonal states, high body mass index, and known genetic predispositions. Prognostication is otherwise based on histopathologic findings and 90% of meningiomas are classified as benign (WHO grade I). Despite use of these prognostic tools, clinicians often observe a more divergent post-operative clinical course. While several pre-clinical studies have identified putative oncogenic influencers, many have failed to show correlation in human trials. Here, we evaluate a single institutional meningioma database stratified by geodemographic and clinical data to identify novel integrated prognostic indicators for aggressive tumor natural history. Our database contains 3, 528 image-confirmed meningiomas between 1992–2019. This report focused on 415 pathology-confirmed cases between 2006–2019: WHO grades I, II, III were 73% (n=303), 25% (n=103), and 2% (n=9) respectively, 71% female predominance (n=294), median age at diagnosis 57-years-old, and 97.5% were white race. Thus far, full exome sequencing has been completed on >50% of cases and >80% have available tumor tissue for future testing as part of this rural Pennsylvania database with high incident aggressive and/or multiply recurrent meningiomas. We selected four representative cases to compare post-operative prognostication to observed clinical outcomes and provide molecular/genetic, histopathologic, treatment modality, comorbid, and other clinical features associated with morbidity/mortality. Included in this patient review is the first reported case of a rare (< 1%) chordoid meningioma, multiply recurrent despite 8-years of aggressive treatment modalities, including surgery, radiation, chemotherapy and androgen-blockade, with eventual extracranial metastasis to the lung, a meningiocarcinoma, if you will. Thorough interrogation of the completed database could yield novel predictive indicators of clinically aggressive meningiomas and guide clinical decision-making for optimized surveillance in high-risk patients.